Does Tax Saving Moderate the Effect of Capital Structure on Firm Performance? An Empirical Research of Indonesian Construction Firms - Azalea Wibisono Sarwoko; Viverita (Jurnal Manajemen Teori dan Terapan)
Objective: This study aimed to empirically examine the impact of capital structure and the moderating effect of tax savings on firm performance of Indonesian SOEs and public construction firms.